2006
DOI: 10.1016/j.ymthe.2005.11.008
|View full text |Cite
|
Sign up to set email alerts
|

CNS-directed AAV2-mediated gene therapy ameliorates functional deficits in a murine model of infantile neuronal ceroid lipofuscinosis

Abstract: The neuronal ceroid lipofuscinoses (Batten disease) are a group of inherited neurodegenerative diseases characterized by the progressive intralysosomal accumulation of autofluorescent material in many cells, visual defects, seizures, cognitive deficits, and premature death. Infantile neuronal ceroid lipofuscinosis (INCL) has the earliest onset ( approximately 1.5 years of age) and is caused by a deficiency in the lysosomal enzyme palmitoyl protein thioesterase-1 (PPT1). Currently there is no effective treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
116
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 43 publications
12
116
1
Order By: Relevance
“…Based on a previous study that showed that intrathecal delivery of recombinant PPT1 enzyme could minimally improve the disease phenotype of Ppt1 −/− mice (31), we delivered AAV2/9-hPPT1 intrathecally to target the spinal cord. We also combined this approach with braindirected gene therapy (12,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on a previous study that showed that intrathecal delivery of recombinant PPT1 enzyme could minimally improve the disease phenotype of Ppt1 −/− mice (31), we delivered AAV2/9-hPPT1 intrathecally to target the spinal cord. We also combined this approach with braindirected gene therapy (12,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tested whether intrathecal (IT) injections of an AAV2/9-hPPT1 vector, either alone or in combination with intracranial (IC) injections (12,(24)(25)(26)(27), would have any beneficial effect on disease progression and brain and spinal cord pathology.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…After Lagenaria siceraria administration the animals used to cross the rod approximately in just 2 seconds as against the control reading which is approximately 9 seconds. This effect of Lagenaria siceraria on stationary rod activity may be due to its effects on neurotransmitter levels, especially acetylcholine (Ach) because the literature shows that the herbs which have been proven as memory enhancers have shown their effects by influencing cholinergic system and by changing neuronal morphology [25][26] .…”
Section: Discussionmentioning
confidence: 99%